Sublethal effects of chlorantraniliprole on Paederus fuscipes (Staphylinidae: Coleoptera), a general predator in paddle field. (15th December 2021) - Khan, Muhammad Musa; Hafeez, Muhammad; Elgizawy, Karam; Wang, Hanyu; Zhao, Jing; Cai, Wanlun; Ma, Weihua; Hua, Hongxia
Abstract: Paederus fuscipes is a general predator in rice fields and a non-target organism of chlorantraniliprole, an effective insecticide for insect-pest control in paddy fields. Pesticide hazards to non-target organisms have been a growing global problem for decades. This study was designed to evaluate the toxicity of chlorantraniliprole at lethal and sublethal levels against P. fuscipes larvae and adults. The LC50 of chlorantraniliprole against P. fuscipes adults and larvae were respectively 535.49 and 111.24 mg a.i. L −1, which is higher than the dosage recommended for use in the field (59.38 mg a.i. L −1 ), but the LC30 and LC10 for larvae are lower than the recommended field dose which showed that the sublethal effects on immature stages are inevitable. Treatment at larval stage with LC30 of chlorantraniliprole significantly elongated the pre-imaginal developmental and pre-oviposition periods. Also, adults exposed directly to chlorantraniliprole oviposited significantly less number of eggs in both LC10 and LC30 treatments. Furthermore, the larval predation efficiency and female bodyweight were also reduced due to exposure to sublethal doses. Meanwhile, the activities of antioxidant (SOD, POD and CAT) and detoxification (P450, AChE and GST) enzymes were also significantly affected by the exposure to these sublethal concentrations. These findings showed that sublethal doses of chlorantraniliprole adversely influenced P. fuscipes development and physiology, and therefore its use as part of integrative pest management should be given further considerations. Highlights: Chlorantraniliprole showed low toxicity to 2nd-instar larvae and adults of P. fuscipes . Sublethal dosage elongated the pre-imaginal developmental period and pre-oviposition period. Sublethal dosage reduced female fecundity, bodyweight and larval predation rate. The antioxidant and detoxification enzyme activities were also significantly affected.